Lietuva ir Estija – skirtingi įvaizdžiai: drąsi šalis ir Šiaurė su polėkiu - Martišius, Mantas (Information & Media, 2009)
Straipsnyje nagrinėjamas šalies įvaizdžio kūrimas ir jo sąsaja su tapatumu. Aptariama įvaizdžio ir šalies prekės ženklo kūrimo specifika. Nagrinėjamas tapatumo, kaip įvaizdžio kūrimo atspirties, klausimas. Globalizacijos kontekste aptariamas regioninio tapatumo susiformavimas ir jo įtaka įvaizdžio kūrimui. Išskiriamas Šiaurės šalių regiono ir regioninio tapatumo susiformavimas. Nurodomos priežastys, kodėl Estijai iš dalies pasisekė sukurti sėkmingą įvaizdį, o Lietuva vis dar negali rasti jai tinkamo įvaizdžio formavimo būdo. Pateikiami nacionalinio prekės ženklo kūrimo atspirties taškai.Lithuania and Estonia – different images: “a bold country” and “a dashing Nordic”Mantas MartišiusSummaryThe importance of the nation’s image today has extremely increased. A lot of states make efforts to construct their positive image. It is a long process, and the most effective way to construct a nation’s image is to convey the characteristics and traits that you would like to present to a wider public. The author scrutinizes the conduct of a nation and the national brand and its interaction with self-identity. He discusses the specific features of the nation’s image and the nation’s brand in the context of the nation’s identity and to points the importance of a region’s self-identity and its impact on the nation’s image. The purpose of the article is, in the context of self-identity, to discuss the nation’s image of Estonia and Lithuania, to emphasize the different Estonian and Lithuanian ways of constructing the nation’s image. The article indicates the reasons why Estonia has managed to construct a successful state image, while Lithuania still cannot find the right path to constructing a suitable state image.The nation’s brand notion covers such commercial and material grounds as investments or incoming tourism. The article disputes that such a way is not the best way construct nation’s image. The notion of the nation’s image is broader than the notion of the nation’s brand. Despite commercial ground, the nation’s image also encompasses such factors as state prominence, the surrounding opinion or the foreigners’ associations and thoughts about the country. Therefore, the image of a nation is more suitable than the nation’s brand.During the construction of the nation’s image it is highly recommended to refer to the nation’s identity. The nation’s image should always grow from its identity. Both expressions are deeply indoctrinated in the collective sense. Today, the conduct of the nation’s image should also reflect a wider context. The nation’s image should overstep the nation’s notion and refer to a lager regional context. Constructing the nation’s image, Estonia is doing exactly so, it attaches the post-soviet state to Nordic countries, the most developed region in the world Tallinn presents itself as another Nordic country, and because of the different historical circumstances, Estonia poses itself as “Nordic with twist”.Lithuania faces the crisis of self-identity, that’s why it shifts form one nation’s image to another. Because Lithuania disputes on self-identity, the nation’s image cannot reflect or refer to the nation’s identity. This causes the construction of the nation’s image on such slogans as “Lithuania is a brave country”. Unfortunately, such construct does not refer to the broader region extent and Lithuania cannot attach itself to an already promoted and well communicated message. Besides, the braveness of Lithuanians should be proven, and it does not refer to such important issues as, for example, the investment possibilities in the state.National brand is a construct influenced by economic and political preferences. A state can deliberately choose what to emphasize to foreign public. Estonia paid attention to its Nordic identity, and Lithuania could also do the same thing. In this case, the communication message would be modern and adaptable, although it has no solid historical roots, but the national brand does not need them. National brand, differently from national image, is oriented to future and not to the past. The present situation and future willingness are more important for creating national brand than the historical background.The Nordic always was the alternative for Lithuania. Self-identity and nation’s image are constructs and can me modified or reconstructed. It is highly possible that in future Lithuania will construct its image on the Nordic ground. The possibility to present Lithuania with the slogan “Lithuania feels the Nordic heat” is still open.